In memory of Ferenc Kratochwill. The situation of the victim in criminal proceedings – as he saw it and as it is now (Academic Journal of Internal Affairs, 2024)
The study is based on the lecture given at the commemoration of the 80th birthday of Dr. Ferenc Kratochwill, in which the main stages of the changes in the procedural regulation affecting the situation of the victim are presented.
Keywords: Ferenc Kratochwill; victim; regulation